An exploratory study of reverse exchange systems used for medical devices in the UK National Health Service (NHS). Issue 2 (14th March 2016) - Xie, Ying; Breen, Liz; Cherrett, Tom; Zheng, Dingchang; Allen, Colin James
Abstract : Purpose: – This study aims to provide insights into the scale and use of information and communication technology (ICT) in managing medical devices in the National Health Service (NHS), with a focus on reverse exchange (RE) systems as a part of the broader reverse logistics (RL) systems, within which medical devices are returned and exchanged. Design/methodology/approach: – Two case studies were conducted with NHS Hospital Trusts, whilst another was built upon secondary resources. Primary findings were triangulated with the information collected from the NHS Trusts' reports, direct observation and a preliminary round of consultations with 12 health-care professionals working in other NHS Trusts or Integrated Equipment Community Services. Findings: – The findings of this paper suggest that the sophistication of ICT implementation increases with the risks and value associated with medical devices. Operational attributes are derived from ICT implementations which can positively affect RE performance. The forces that drive the adoption of ICT in the NHS include pressure from government, business partners and patients; competitive pressure; perceived benefits; organisation size; top management support; and the availability of sufficient resources. Obstacles are mainly centred around the lack of sufficient resources. Research limitations/implications: – Although the trusts that participated in this research are representative of different regions, the generalisation of the study results may be limited by the size of the sample organisations, so the results can only provide insights into the research problem. As this work is exploratory in nature, there is insufficient data on which to form definitive recommendations. Practical implications: – NHS Trusts may use the six operational attributes identified and verified by the case studies to benchmark their ICT implementation for device management. The actual and potential benefits of ICT implementation could inform technology development and encourage the uptake of ICT in healthcare. Governmental bodies can utilise this information to develop directives to actively drive ICT adoption in device management and the associated RE system. A well-considered training programme is needed to improve staff ICT skills to fully realise the potential of ICT systems which support the effective RE of medical devices. Originality/value: – The results of this paper suggest that the reverse management of medical devices backs up the supply chain attained through using ICT, which in turn reduces capital costs, medical risk and increases the finance available for frontline medical treatment.